4CPS-007 Targeting patients with pneumonia by COVID-19 that could be beneficiated by colchicine. Issue 1 (23rd March 2023) - Villamañán, E; Sobrino, C; Mateos, C; Collada, V; Hoyo, A; Mallón, S; Pavón, J; Jiménez, I; Larrubia, Y; Herrero, A
Abstract : Background and Importance: Available data reported different results about the effect of colchicine in patients with COVID-19 pneumonia (CN) proving the need for more analysis. Currently, many of these patients are treated with high-cost new drugs with poor results. Aim and Objectives: To evaluate whether treatment with colchicine added to the standard therapy for CN was related to deaths reduction. Secondary objectives: to analyse differences in length of stay (LOS) and combination of drugs in treatment protocols with better results. Material and Methods: Multicentre, real-world, controlled, retrospective cohort study(March-June2020). Inclusion criteria: hospitalised adult patients with CN. Admitted to critical care units were excluded. Experimental group: Patients treated with colchicine who met inclusion criteria (colchicine therapy group [CG]). Control group: those who met inclusion criteria and did not received colchicine (non-colchicine therapy group [NCG]). Patients were matched 1:1 by age ( ± 2years), sex, severity of the disease and comorbidity. To select controls, we chose the consecutively next admitted patient after one treated with colchicine. This allowed us to select control subjects at a close time and place to cases, that is, under similar circumstances in terms of patient care protocols. Results: 222 (111 treated with colchicine) patients were analysed. Median age 79 years [66–88] (81 years [66-87] in CG vs 79 years [66-88] in NCG, p=0.978). 52.3% men (54.1% CG vs 50.5% NCG; p=0.591). Primary endpoint of death occurred in 19 (17.1%) patients in the CG as compared with 32 (29.4%) in the NCG (OR: 0.497; 95% CI: 0.261–0.946; p=0.031). Hospital LOS was dichotomised by the median value (10 days), the use of colchicine was associated with a longer hospital LOS when comparing with the control group (OR=1.856; 95% CI:1.089–3.162; p=0.022). Proportion of deaths were higher in NCG than in CG in patients ≥70 years (p=0.012). With respect to sex and comorbidity, distribution of deaths showed no significant differences. Almost all patients received antimicrobials (91.9%) concomitantly, death rate: 19/50 (38%) CG vs.31/50 (62%) NCG; p=0.023), by antimicrobial: azithromycin (9/19) (47.4%) in CG vs.10/19 (52.6%) NCG; p=0.517; ceftriaxone16/44 (36.4%) CG vs 28/44 (63.6%) NCG; p=0.022 and levofloxacin 4/12 (33.3%) CG vs 8/12 (66.7%) NCG; p=0.232. Conclusion and Relevance: Our study showed lower mortality in hospitalised patients who received colchicine to treat CN. This treatment was particularly beneficial for elderly treated with antibiotics concomitantly. Findings in our study support the need of more randomised clinical trials that could fully elucidate the type of patients who may potentially benefit from this low-cost drug. References and/or Acknowledgements: 1. Kalil AC. Treating COVID-19-Off-Label Drug Use, Compassionate Use, and Randomized Clinical Trials During Pandemics. JAMA 2020;323 (19):1897–1898. Conflict of Interest: No conflict of interest